Nursing student extension experience in a school health and sexuality education project - Knopp Ribeiro, Daniele; da Silva Vieira, Maria Theresa; Rodrigues Carvalho, Tamiris; da Silva Pinheiro, Ana Paula; Ribeiro de Jesus, Rodolfo; de Oliveira Freitas, Fabiana; dos Reis Santos, Sueli Maria; Pinto de Jesus, Maria Cristina (Guará Journal, 2018)
It is an experience report on educational actions carried with adolescents, from 2014 to 2016. The objective of this study was to describe and discuss the extension experience of nursing students in a health and sexuality education project in the school as part of undergrad-uate teaching at a public university in the State of Minas Gerais. The activities included participation in the planning, execution and evaluation of discussions on adolescent health and sexuality, as well as apprehension of methodologies active teaching and research techniques. The experience gave students the appropriation of knowledge and skills required for the professional training of nurses